Acetyl-CoA synthesis in the skin is a key determinant of systemic lipid homeostasis - Phuong T.T. Nguyen; Mia Shiue; Nina Kuprasertkul; Pedro Costa-Pinheiro; Luke T. Izzo; Laura V. Pinheiro; Hayley A. Affronti; Gabriel Gugiu; Shivani Ghaisas; Joyce Y. Liu; Jordan C. Harris; Charles W. Bradley; et al. (Cell Reports)
Summary: ATP-citrate lyase (ACLY) generates cytosolic acetyl-coenzyme A (acetyl-CoA) for lipid synthesis and is a promising therapeutic target in diseases with altered lipid metabolism. Here, we developed inducible whole-body Acly-knockout mice to determine the requirement for ACLY in normal tissue functions, uncovering its crucial role in skin homeostasis. ACLY-deficient skin upregulates the acetyl-CoA synthetase ACSS2; deletion of both Acly and Acss2 from the skin exacerbates skin abnormalities, with differential effects on two major lipid-producing skin compartments. While the epidermis is depleted of barrier lipids, the sebaceous glands increase production of sebum, supplied at least in part by circulating fatty acids and coinciding with adipose lipolysis and fat depletion. Dietary fat supplementation further boosts sebum production and partially rescues both the lipoatrophy and the aberrant skin phenotypes. The data establish a critical role for cytosolic acetyl-CoA synthesis in maintaining skin barrier integrity and highlight the skin as a key organ in systemic lipid regulation.